Biallelic hypomorphic variants in ALDH1A2 cause a novel lethal human multiple congenital anomaly syndrome encompassing diaphragmatic, pulmonary, and cardiovascular defects. Issue 5 (1st April 2021) - Beecroft, Sarah J.; Ayala, Marcos; McGillivray, George; Nanda, Vikas; Agolini, Emanuele; Novelli, Antonio; Digilio, Maria C.; Dotta, Andrea; Carrozzo, Rosalba; Clayton, Joshua; Gaffney, Lydia; McLean, Catriona A.; et al.
Abstract: This study shows a causal association between ALDH1A2 variants and a novel, severe multiple congenital anomaly syndrome in humans that is neonatally lethal due to associated pulmonary hypoplasia and respiratory failure. In two families, exome sequencing identified compound heterozygous missense variants in ALDH1A2 . ALDH1A2 is involved in the conversion of retinol (vitamin A) into retinoic acid (RA), which is an essential regulator of diaphragm and cardiovascular formation during embryogenesis. Reduced RA causes cardiovascular, diaphragmatic, and associated pulmonary defects in several animal models, matching the phenotype observed in our patients. In silico protein modeling showed probable impairment of ALDH1A2 for three of the four substitutions. In vitro studies show a reduction of RA. Few pathogenic variants in genes encoding components of the retinoic signaling pathway have been described to date, likely due to embryonic lethality. Thus, this study contributes significantly to knowledge of the role of this pathway in human diaphragm and cardiovascular development and disease. Some clinical features in our patients are also observed in Fryns syndrome (MIM# 229850), syndromic microphthalmia 9 (MIM# 601186), and DiGeorge syndrome (MIM# 188400). Patients with similar clinical features who are genetically undiagnosed should be tested for recessive ALDH1A2‐deficient malformation syndrome. Abstract : Biallelic variants in ALDH1A2 cause a novel developmental anomaly syndrome. Each variant seen in patients was highly conserved, and caused functional changes as determined by in‐silico protein modelling and functional assays.